LEACHING OF MANGANESE ORES FROM NUSA TENGGARA USING OXALIC ACID AND MOLASSES AS REDUCING AGENTS AND SYNTHETHIC OF MANGANESE DIOXIDE POWDER BY HYDROTHERMAL METHOD - SUMARDI (NIM : 22110024), SLAMET
Manganese is the fourth most used metal after iron, aluminium and copper. High content of manganese ores is process through pyrometalurgic method to produce ferro manganese and silicon manganese which keep increasing. While low content of manganese ores is processed by hydrometalurgic. The experiment for this thesis is to study manganese ores reductive leaching using oxalic acid and molasses as reductive agents and synthetic processs of manganese dioxide (MnO2) as leaching result using hydrothermal method. Series of leaching tests have been carried to study the influences of sulfuric acid concentration, leaching temperature, solid percentage and types of reductors on the manganese extraction percentage and co-dissolution of iron. Based on the investigation results, best condition which results in the highest Mn extraction with regard to sulfuric acid concentration, temperature, solid percentage and reductor type is specified. Kinetics behaviour of mangan leaching was predicted by using Shrinking Core and Shrinking Particles Models and reactan rate constant, rate-determining step and activation anergy for mangan leaching was determined. Synthesis of manganese dioxide was performed by using kalium permanganate as precursor. The effects of heating time and MnSO4/KmNO4 ratio on the characteristic of the product was evaluated. The synthesis product was analyzed by XRF, XRD, SEM and TEM to determine the product purity, size and morphology of the MnO2 particle. Leaching experiment using oxalic acid as reductor yield the highest extraction percentage of manganese (69,92%) with 6% sulfuric acid, 80 oC, 10% solid, 200 rpm mixing speed, 30 g/L oxalic acid. Highest manganese extraction (95,33%) is achieved by manganese ores reductive leaching using molasses as reductive agents and sulfuric acid. This can achieved on 6% sulfuric acid concentration, 70 oC temperature leaching, 10% solid, 100 g/l molasses, 200 rpm mixing speed. Kinetic study on manganese leaching using molasses as reductive agent shows that the first stage of leaching process (<5 minutes) is controlled by surface reaction with activation energy 11,56 kkal/mol. Intermediate stage (10<t<360 minutes), determine factore is reactant diffusion through unreacted product and surface reaction. In manganese dioxide synthesis experiment using hydrothermal method, MnO2 SEM analysis through various time of crystallisation and precursor composition is having similar structure one compare to others with various size between 520 nmm through 1,05 micrometer. XRF analysis shows that MnO2 yield from the experiment is similar to MnO2 produced by Merck, with 2,4 % K2O impurities diffence.